Controlled Existence in Zimbabwe and Beyond: Exploring Survivability in Shadows (2012) by Novuyo Rosa Tshuma and The Border Jumper (2019) by Christopher Mlalazi - Makoni, Brightman (University of the Witwatersrand, Johannesburg, 2022)
This study considers existence and survivability as the particulars of transnational migration. Through critical engagement with Novuyo Rosa Tshuma’s Shadows (2012) and Christopher Mlalazi’s The Border Jumper (2019), the research explores migrant lives in the context of transborder migration between Zimbabwe and South Africa. The chosen literary texts are analysed through the prism of typified migrant characters’ lives in Zimbabwe, South Africa and on the margins of both and on the borderlines, between societies and countries. Insights are drawn from the theory of intersectionality entwined with concepts of oppression, identity and habitus. The unified theoretical framework is applied on migrant characters’ trend of existing and surviving and how the trends expose power dynamics that play out in one’s mother country and beyond borders as a consequence of identity fluidity, place, space and time.
A research report submitted to the Faculty of Humanities, School of Social Sciences, at the University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Critical Diversity Studies by Coursework and Research Report, in 2022.
Keywords: Existence; Survivability; Zimbabwe; South Africa; Trans-border migration; Power dynamics; UCTD; SDG-16: Peace, justice and strong institutions